AGE-DEPENDENT CHARACTERISTICS OF EPIDEMIOLOGICAL PROCESS OF HEPATITIS A IN FEDERAL DISTRICTS OF RUSSIA AT CURRENT PERIOD OF TIME. BASIS OF THE NECESSITY OF SCHEDULED VACCINATION AGAINST HEPATITIS A IN CHILDREN - S. L. Mukomolov; I. A. Levakova; A. V. Stalevskaya (Педиатрическая фармакология)
Recently epidemiological data on maximal hepatitis A (HA) morbidity values shift to older age groups, including adolescents at the age of 15–19 years and young adults at the age 20–39 years, and decreasing significance of children as a risk group have been published. These phenomena have not been well studied and do not have satisfactory explanations. The aim of this study was to evaluate age dependent characteristics of epidemiological process of HA in Russian Federation and its federal districts during the current period of time and to determine the necessity and appropriate age of scheduled vaccination against this infection in children. The comparative analysis of age-dependent values of HA morbidity (percentage of children and adults, the rate of adults and children values, intensity) of the population in federal districts of Russian Federation in 1999, 2001 and 2010 was performed. It was established, that HA is still a significant challenge in children health in Russian Federation. The percentage of children at the age of 0–14 years among the developed the disease in 2010 (28%) does not differ significantly from that in 1999 (40%). In Far Eastern, Siberian and North-Caucasian federal districts the children morbidity constantly 4–6 times exceeds the respective values in adults. Such characteristics of HA epidemiology indicate the necessity of scheduled vaccination of children against this infection.